Analysis of Hedging and Profit of Indonesian Manufacturing Companies - Rahmat Hidayat; Hasrul Azwar Hasibuan; Samrin (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This research aim to test and know clearly“ Analyze hedging to increase profit manufacture company in Bursa Efect Indonesia 2013-2016. This research used quantitative methods that involved 12 company. The data was collected by financial statement from Bursa Efect Indonesia. Data were analyzed using a statistical formula, namely by using pane and ardll regression analysis of the processing performed by eviews versy 7..Resultsofregression analysisis :Y =378,46 + 165.86X1+9.74X2+1.85X3 + e. The result of quantitative analysis showed that as simultant DER, ROA, dan CR have influent to Profit. As partial DER and ROA have no significant influence to profit but CR have significant influence to Profit.